Indo-Pacific finless porpoises presence in response to pile driving on the Jinwan Offshore Wind Farm, China - Fang, Liang; Li, Min; Wang, Xinxing; Chen, Yujian; Chen, Tao (Frontiers in Marine Science, 2023)
The Jinwan Offshore Wind Farm project in the Pearl River Estuary (PRE) is a new stressor for the resident marine mammals there, especially for the Indo-Pacific finless porpoise. A broadband recording system was deployed in the Jinwan Offshore Wind Farm, before and during the construction period, in order to determine how the finless porpoise responded to pile driving activity. The results showed that the wind farm area was an important habitat for the finless porpoise during the monitoring period. The finless porpoise also showed avoidance behavior of pile driving activity. There was a significant negative correlation between porpoise detection and pile driving detection, and the time between porpoise’s acoustic detections increased during pile driving compared to periods without pile driving. Our results indicated that acoustic protection measures are strongly recommended in future offshore wind farm developments in order to protect finless porpoises.